Report of the Special Committee on the Situation with regard to the Implementation of the Declaration on the Granting of Independence to Colonial Countries and Peoples for 2012 - United Nations Department for General Assembly; Conference Management (United Nations, 2012)
Official Records of the Report of the Special Committee on the Situation with Regard to the Implementation of the Declaration on the Granting of Independence to Colonial Countries and Peoples for 2012.